The Contribution of Dr. Mumtaz Hussain Pathan in the History of Sindh - Khatti , Deedar Hussain; Soomro, Ghulam Rasool; Shah, Saeedah (Progressive Research Journal of Arts & Humanities (PRJAH), 2022)
The present study compiles the contribution of Dr. Mumtaz Hussain Pathan in the history of Sindh. This research study utilizes the secondary data from different reliable sources, i.e., digital libraries, newspapers, books and so forth. Besides, the researcher contacted the relatives of Pathan and the historians for further knowledge related to Pathan. This study bestows the outcomes in literature and the history readers as well as the benefits follow the study roots in writing profiles of contributory personalities. The study finds out that Pathan has significantly contributed to the history of Sindh by pursuing a scientific research-based approach. The study touches the core of the cream contribution providing the genuine and original facts figures. It helps to eliminate factionalized hypotheses from the history of Sindh in light of Pathan’s contribution. The study would be helpful to research other aspects of Pathan with respect to the history of Sindh. The study also signifies to implicate the Sindh’s history, and the findings play the vital role in highlighting the contribution of Pathan. The research outcomes would further open the windows of future research in the different personality traits of Pathan.